2018
DOI: 10.3390/ijerph15102076
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between the Dopamine D4 Receptor and DAT1 Dopamine Transporter Genes Polymorphisms and Personality Traits in Addicted Patients

Abstract: Many factors are involved in addiction. The dopaminergic system is thought to be the key element in this process. The mesolimbic dopamine system is a crucial element in the reward system. Changes in this system are thought to be leading to substance use disorders and dependence. Therefore, for our study we chose an analysis of two polymorphisms in genes (Variable Number of Tandem Repeats in DRD4 and DAT1) responsible for dopaminergic transmission, which might be implicated in the scores of personality traits m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Some studies have been carried out associating DAT 3′UTR VNTR polymorphism and neuroticism, and most of them did not find significant results (Chmielowiec et al, 2018;Hünnerkopf, Strobel, Gutknecht, Brocke, & Lesch, 2007;Kazantseva, Gaĭsina, Malykh, & Khusnutdinova, 2009;Kazantseva, Gaysina, Malykh, & Khusnutdinova, 2011). However, a recent meta-analysis has suggested that the dopaminergic system is related to personality trait differences in neuroticism only in contexts where there is a high climatic stress (Fischer et al, 2018).…”
Section: Dopaminergic System and Neuroticismmentioning
confidence: 99%
“…Some studies have been carried out associating DAT 3′UTR VNTR polymorphism and neuroticism, and most of them did not find significant results (Chmielowiec et al, 2018;Hünnerkopf, Strobel, Gutknecht, Brocke, & Lesch, 2007;Kazantseva, Gaĭsina, Malykh, & Khusnutdinova, 2009;Kazantseva, Gaysina, Malykh, & Khusnutdinova, 2011). However, a recent meta-analysis has suggested that the dopaminergic system is related to personality trait differences in neuroticism only in contexts where there is a high climatic stress (Fischer et al, 2018).…”
Section: Dopaminergic System and Neuroticismmentioning
confidence: 99%
“…Their findings provide evidence of the lethal consequences of substance abuse in an unobtrusive manner. Moreover, Chmielowiec et al [46] examined the relationship between the mesolimbic dopamine system and addiction in a group of 299 addicted subjects and another group of 301 non-addict controls by analyzing two polymorphisms in their genes (a variable number of tandem repeats in DRD4 and DAT1), which are mainly responsible for dopaminergic transmission, representing a human reward system that is closely related to substance abuse and misuse. It is clear that research using different methods and designs is useful in fortifying and enhancing currently established concepts and knowledge of substance abuse.…”
Section: Researching Substance Abuse: Methods and Designsmentioning
confidence: 99%
“…While van Gestel et al (438) reported an association between DAT1 VNTR polymorphisms and novelty seeking, a personality trait associated with SUDs (439), other studies have failed to replicate this finding (440, 441).…”
Section: The Dopamine Systemmentioning
confidence: 99%